A Comparative Study of Academic Achievement among Senior Secondary Students in relation to types of Parental Engagement - Dr. Aruna Anchal, Meenu, (International Journal of Advanced Research and Multidisciplinary Trends (IJARMT), 2025)
The present study investigated senior secondary school students’ academic achievement in relation to their parent types of engagement. Given the critical role that parents play in their students’ education performance, it was important to develop a better understanding of which types of parent engagement had the most significant impact. To that end, this research utilized a descriptive survey design and selected 600 students from Classes XI and XII in Haryana. The students were sampled using the stratified random sampling technique, with gender and school type as strata. Academic achievement was defined as the most recent examination score, while the level of parent engagement was measured via a self-constructed scale validated by experts. Descriptive statistics, ANOVA, and post-hoc Tukey HSD tests were employed to analyze the data. The results show a defined, significant difference in the students’ performance based on their parents’ types of engagement. Indeed, students with low, average, and high engagements scored differently, with the latter group achieving the highest mean academic scores, the average following, and the former having the lowest scores. Post-hoc analysis showed that the three groups significantly differed from each other, underscoring the strong positive correlation between parent engagement and student performance. The study calls for schools and other education policymakers to promote parent engagement through structured programs and awareness campaigns.